Development of appropriate technology for converting cassava peel biomass with sugar cane peel into bioethanol - Irawan, Ibnu; Widiaswanti, Ernaning; Pranjoto, Hartono; Choir, Qalibun Ghalidh (Widya Teknik, 2025)
Alternative fuels are waste-derived materials that can be converted into substitutes for petroleum-based fuels. Alternative fuels can be derived from agricultural waste, which is often underutilized and no longer viable for direct use. Among various types, cassava peels and sugarcane peels are promising feedstocks for bioethanol production due to their high carbohydrate and glucose content. Cassava and pineapple peels are rich in fermentable sugars, making them suitable for producing liquid fuels such as bioethanol with concentrations exceeding 80%. The fermentation results of these materials were followed by distillation at 80°C to obtain initial stage of bioethanol. The highest water content of 76% was recorded at a fermentation time of 9, while the maximum bioethanol yield reached 35.2%, with a corresponding calorific value of 1490.46 kcal/kg. At the same fermentation duration, the lowest flash point was observed at 20°C. This low flash point indicates that the resulting bioethanol evaporates easily at lower temperatures, a behavior influenced by the fuel's density and water content. Furthermore, significant interactions were observed between the raw material composition, the addition of EM4 bioactivator, and yeast during fermentation. These factors collectively influenced the methane (CH4) content generated, highlighting their role in optimizing the fermentation process.